Pendekatan Ma’na Cum Maghza Tentang Pemimpin Non Muslim (Analisis Terhadap Al-Maidah:51) - Yuliati, Putri; Qardlawi, Muhammad Yusuf; Wulandari, Maharani (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2022)
This article examines the discourse on non-Muslim leadership through the lens of surah al-maidah verse 51. Because surah al-maidah verse 51 is often used as a reference for prohibiting non-Muslims from becoming leaders. This type of research is library research. This writing will focus on discussions of a literary nature, the study of which is by searching and reviewing various library materials that will be used by the author. This research uses the ma'na cum maghza hermeneutic approach initiated by Sahiron Syamsuddin. After researching using the ma'na cum maghza approach, there is no absolute prohibition in religion that forbids someone who is a non-Muslim from becoming a leader, as long as it does not cause harm. This is because leadership is an ability and readiness that a person has to be able to care for, supervise and protect the people they lead. Then, Indonesia is a nation state that does not adopt Islamic law as the basis of the state, and practices the concept of democracy, so that the appointment of leadership from non-Muslim circles in the country is permitted as long as it brings benefits.